Increasing Soil Bearing Capacity and Shear Modulus with Recycle Concrete Aggregate - Pertiwi, Sheila Ananda Putri; Candra, Agata Iwan; Karisma, Dwifi Aprillia; Ali, Mahardi Kamalika Khusna (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2024)
Soil is an important component in building construction because it supports the structure. Clay soils often pose problems due to their high potential for swelling and shrinkage, which can result in cracking and building settlement. Stabilization of clay soil is an important solution. This research aims to evaluate the effect of recycled aggregate concrete (RCA) from laboratory construction waste on the characteristics of clay soil. The research method involved laboratory experiments, with a mixture of clay and RCA at 5%, 10%, and 15% variations. Testing includes Atterberg Limit, Standard Proctor Test, and Unconfined Compressive Strength (UCS). The results showed that adding RCA increased clay soil's bearing capacity and shear modulus. The peak bearing capacity was achieved by adding 5% RCA, with a Qu value reaching 265.24 kN/m². The shear modulus also increased from 41.63 MPa to 62.442 MPa with the addition of 5% RCA. Thus, the addition of RCA from laboratory construction waste can increase the bearing capacity and shear modulus of clay soil to support construction safety and the principles of sustainable development.